Tactile to vibrotactile sensory feedback interface for prosthethic hand users - Mohamad Hanif, Noor Hazrin Hany; Chappell, Paul H.; White, Neil M.; Nik Hashim, Nik Nur Wahidah (IEEE, 2016)
The motivation of this research work is to provide a sense of embodiment to prosthetic users by supplementing their devices with sensory feedback to the residual upper arm. This sensory feedback replicates the tactile sensory system of glabrous skin that covers palm and flexor surfaces of fingers. In this work, we produced vibration patterns that will be perceived at the upper arm, according to signals obtained by a prosthetic finger when sliding across fabricated textured surfaces. This was done by transforming the signals to ‘on’ and ‘off’ pulses in the LabView environment and then forwarded to a data acquisition board to provide voltage signals to a vibration actuator. We implemented a novel frequency measurement procedure to maintain a vibration frequency of 250 Hz, which is the optimum frequency of the mechanoreceptors underneath the skin of the upper arm in detecting vibration. The outcome from this research work leads to optimistic possibility that a touch sensation that was previously lost could be restored to different parts of the body. This undoubtedly will increase users’ acceptance of the device as a part of their body due to its ‘life-like’ quality.